Epidemiology of rotavirus diarrhea among children less than 5 years hospitalized with acute gastroenteritis prior to rotavirus vaccine introduction in India. Issue 51 (3rd December 2020) - Girish Kumar, C.P.; Giri, Sidhartha; Chawla-Sarkar, Mamta; Gopalkrishna, Varanasi; Chitambar, Shobha D.; Ray, Pratima; Venkatasubramanian, S.; Borkakoty, Biswajyoti; Roy, Subarna; Bhat, Jyothi; Dwibedi, Bhagirathi; Paluru, Vijayachari; et al.
Abstract: Background: Rotavirus is an important cause of severe diarrhea requiring hospitalization, accounting for approximately 78, 000 deaths annually in Indian children below 5 years of age. We present epidemiological data on severe rotavirus disease collected during hospital-based surveillance in India before the introduction of the oral rotavirus vaccine into the national immunization schedule. Methods: The National Rotavirus Surveillance Network was created involving 28 hospital sites and 11 laboratories across the four geographical regions of India. From September 2012 to August 2016 children less than 5 years of age hospitalized for diarrhea for at least 6 h, were enrolled. After recording clinical details, a stool sample was collected from each enrolled child, which was tested for rotavirus antigen using enzyme immunoassay (EIA). Nearly 2/3rd of EIA positive samples were genotyped using reverse transcription polymerase chain reaction to identify the G and P types. Results: Of the 21, 421 children enrolled during the 4 years surveillance, 36.3% were positive for rotavirus. The eastern region had the highest proportion of rotavirus associated diarrhea (39.8%), while the southern region had the lowest (33.8%). Rotavirus detection rates were the highest in children aged 6–23 months (41.8%), and 24.7% in children aged < 6 months. Although rotavirus associated diarrhea was seen throughout the year, the highest positivity was documented between December and February across all the regions. The most common rotavirus genotype was G1P[8] (52.9%), followed by G9P4 (8.7%) and G2P4 (8.4%). Conclusions: There is high burden of rotavirus gastroenteritis among Indian children below 5 years of age hospitalized for acute diarrhea thereby highlighting the need for introduction of rotavirus vaccine into the national immunization program and also for monitoring circulating genotypes.